SISTEM INFORMASI PENGOLAHAN DATA PENGGAJIAN KARYAWAN PADA CV. WIJAYA - Adriana, Windy (JURNAL AKADEMIKA, 2016)
The information system of payroll data processing with the good computerized and database support as data storage media will reduce any mistakes when inputting data. CV. Wijaya is a company engaged in the service delivery of fertilizer subsidies from the Government, which will be channeled to authorized distributors and sellers of fertilizers located in the district and sub-district in the province of Jambi. With the information system of payroll data processing that is both as a means of helping to process, edit, calculations are accurate and current data call is to help the user so that the work becomes more effective and efficient in its execution.